The study of radiotherapy resistance of hypoxic tumour for improving survival of cancer patient. - Goh, Yeek Teck. (2013)
Despite the advent of many new targeted cancer therapies, radiotherapy is still considered an important treatment modality in killing localised cancer cells. However, the therapeutic response to ionising radiation is greatly dependent on the oxygenation status of the tumour. Hypoxic tumours are well-established to have association with malignant progression and radioresistance. Interestingly, our preliminary findings revealed that 3Gy of ionising radiation can significantly enhance the survival rates of hypoxic A431 epithelial carcinoma cells rather than killing them. Here we attempt to improve our understanding of the molecular mechanisms of radioresistance and post-irradiation survival of hypoxic cells. In this study, iTRAQ quantitative proteomics approach was employed to determine the protein expression and functional changes induced by γ-radiation and hypoxic condition. Functional annotation and classification revealed the up-regulation of two significant groups of proteins involved in calcium-binding/signalling and actin regulation. These proteins are likely to promote cell survival pathways such as DNA repairs in hypoxic cells upon radiation exposure. In addition, specific glycolytic enzymes and several other candidate proteins were induced during hypoxia to potentially influence cellular radiosensitivity. These results revealed proteins induced under hypoxia and γ-radiation, and provided potential novel targets for designing radiosensitising drug and predicting radiotherapy response.